The Effectiveness Of Preview, Question, Read, Reflect, Recite, And Review (PQ4R) Method With Seesaw Application In Teaching Reading For Vocational High School - Varia Virdania Virdaus; Annisa Rahmasari; Saiful Rifa’i (Journal of Development Research, 2024)
The research objective was to find out the Effectiveness Of Preview, Question, Read, Reflect, Recite, And Review (PQ4R) Method This research was an experimental research focused on quantitative approach. Non-randomized control group pre-test posttest Design was applied. There are two variables: Independent and dependent variable. The independent variable was PQ4R method and dependent variable was the students’ reading comprehension score. The subjects of this research were the first year students of SMK Muhammadiyah 1 Kota Blitar. The research has proved that the teaching reading using Preview, Question, Read, Reflect, Recite, And Review (PQ4R) Method With Seesaw Application has really significant power and give positive impact in improving the students’ reading comprehension skill.